Macrophage phagocytosis - Swanson, Joel (Henry Stewart Talks, 2013)
The importance and targets of macrophage phagocytosis, Phagosome formation & maturation, Roles of receptors, actin cytoskeleton and phosphoinositides during phagocytosis, Target geometry effects on phagocytosis, Signaling for phagocytosis, Phagocytosis of apoptotic cells, Ruffling & macropinocytosis, Microbicidal chemistries in phagosomes, Manipulation by microbes